Biosynthesis of anticancer phytochemical compounds and their chemistry - Dogra, Amandeep; Kumar, Jitender (Frontiers in Pharmacology, 2023)
Cancer is a severe health issue, and cancer cases are rising yearly. New anticancer drugs have been developed as our understanding of the molecular mechanisms behind diverse solid tumors, and metastatic malignancies have increased. Plant-derived phytochemical compounds target different oncogenes, tumor suppressor genes, protein channels, immune cells, protein channels, and pumps, which have attracted much attention for treating cancer in preclinical studies. Despite the anticancer capabilities of these phytochemical compounds, systemic toxicity, medication resistance, and limited absorption remain more significant obstacles in clinical trials. Therefore, drug combinations of new phytochemical compounds, phytonanomedicine, semi-synthetic, and synthetic analogs should be considered to supplement the existing cancer therapies. It is also crucial to consider different strategies for increased production of phytochemical bioactive substances. The primary goal of this review is to highlight several bioactive anticancer phytochemical compounds found in plants, preclinical research, their synthetic and semi-synthetic analogs, and clinical trials. Additionally, biotechnological and metabolic engineering strategies are explored to enhance the production of bioactive phytochemical compounds. Ligands and their interactions with their putative targets are also explored through molecular docking studies. Therefore, emphasis is given to gathering comprehensive data regarding modern biotechnology, metabolic engineering, molecular biology, and in silico tools.